2018
DOI: 10.14744/anatoljcardiol.2018.23682
|View full text |Cite
|
Sign up to set email alerts
|

Study of the association of 17 lipid-related gene polymorphisms with coronary heart disease

Abstract: ObjectiveBlood lipids are well-known risk factors for coronary heart disease (CHD). The aim of this study was to explore the association between 17 lipid-related gene polymorphisms and CHD.MethodsThe current study examined with 784 CHD cases and 739 non-CHD controls. Genotyping was performed on the MassARRAY iPLEX® assay platform.ResultsOur analyses revealed a significant association of APOE rs7259620 with CHD (genotype: χ2=6.353, df=2, p=0.042; allele: χ2=5.05, df=1, p=0.025; recessive model: χ2=5.57, df=1, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Similarly, a case study reported a significant association of APOE rs7259620 with CHD risk in men, instead of in women. 39 Another study has shown that CDKN2BAS rs7865618 is a risk factor for CHD in women. 40 In addition, CYP11B1 rs6410 and rs5283 are significantly associated with an increased risk of CHD in women, but not in men.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a case study reported a significant association of APOE rs7259620 with CHD risk in men, instead of in women. 39 Another study has shown that CDKN2BAS rs7865618 is a risk factor for CHD in women. 40 In addition, CYP11B1 rs6410 and rs5283 are significantly associated with an increased risk of CHD in women, but not in men.…”
Section: Discussionmentioning
confidence: 99%
“…The SNPs were APOE rs7259620, PVRL2 rs403155, TOMM40 rs157581, EXOC3L2 rs10406604, and CD3EAP rs3212986. In Han Chinese (784 with cardiovascular diseases and 730 without cardiovascular diseases) APOE rs7259620 had a positive association with cardiovascular diseases only in men, not women without adjusting for the covariates [ 28 ]. The study explained that the association may be due to gender differences in hormonal profiles, smoking status, alcohol-drinking, occupation, and dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Stx-1A maps in a region 70kb close to one of the genes suggested by GWAS: that is MLX-interacting protein-like (MLXIPL), significantly associated with Coronary heart disease. [42] An in-depth evaluation of the Stx-1A SNPs influence in cardiologic risk is warranted to confirm the involvement of these SNPs in IHD.…”
Section: Discussionmentioning
confidence: 99%